2021
DOI: 10.3389/fpsyg.2020.631033
|View full text |Cite
|
Sign up to set email alerts
|

Music Listening Predicted Improved Life Satisfaction in University Students During Early Stages of the COVID-19 Pandemic

Abstract: Quarantine and spatial distancing measures associated with COVID-19 resulted in substantial changes to individuals’ everyday lives. Prominent among these lifestyle changes was the way in which people interacted with media—including music listening. In this repeated assessment study, we assessed Australian university students’ media use (i.e., listening to music, playing video/computer games, watching TV/movies/streaming videos, and using social media) throughout early stages of the COVID-19 pandemic in Austral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 58 publications
7
60
1
1
Order By: Relevance
“…Results showed that caregivers tended to engage more frequently in music-related activities (e.g., listening to music) during social distancing compared with a typical day before social restrictions. This finding agrees with a general trend revealed by studies showing an increase in the time adults spent on musical activities during the COVID-19 pandemic (Cabedo-Mas et al, 2020;Krause et al, 2020).…”
Section: Caregivers' and Children's Musical Behaviors During Social Dsupporting
confidence: 92%
“…Results showed that caregivers tended to engage more frequently in music-related activities (e.g., listening to music) during social distancing compared with a typical day before social restrictions. This finding agrees with a general trend revealed by studies showing an increase in the time adults spent on musical activities during the COVID-19 pandemic (Cabedo-Mas et al, 2020;Krause et al, 2020).…”
Section: Caregivers' and Children's Musical Behaviors During Social Dsupporting
confidence: 92%
“…Recent studies about music listening in the pandemic have indicated that people have turned to music to provide a sense of togetherness (Fink et al, 2021;Granot et al, 2021), as well as to decrease pandemic isolation-induced loneliness (Martín et al, 2021). Like Krause et al (2020), we found no difference in hours spent listening to music in general across the different time points of the pandemic, as well as no difference in time spent listening to music alone across time periods. However, when using Spotify with others, there was a regular progression in whom they were listening with.…”
Section: Discussioncontrasting
confidence: 48%
“…Although some forms of media like watching television, videos, and movies have been associated with negative life satisfaction during the pandemic, music use has been correlated with positive life satisfaction (Krause et al, 2020). Recent research suggests that people used music more often to cope during the lockdown compared to before (Fink et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of lockdown situations during the COVID-19 pandemic, it has been indicated that music related activities have increased through listening, singing, dancing or playing instruments, and that this has been accompanied by efforts to cope with the stressor at hand (Cabedo-Mas et al, 2021). Additionally, Krause et al (2021) found that life satisfaction within students was higher than normal when individuals increased the time they spent listening to music, suggesting an association between the amount of time spent listening and wellbeing. Therefore, from the strategies laid out in the coping psychology literature, it may seem that those using more emotion-focused coping strategies are more likely to benefit and therefore use music as a mood regulator in response to stress.…”
Section: Dysfunctional Coping Strategiesmentioning
confidence: 99%